Implementation of a Stem-Integrated PJBL Model to Improve Science Processes and Learning Outcomes - Haryanto, Haryanto; Minarni, Minarni (FKIP Universitas Lampung, 2023)
Abstract: This project-based learning research aims to provide alternative problem-solving in the Biochemistry II course to improve students' scientific process abilities and learning outcomes in solving a problem. Quantitative data on student learning outcomes C4, C5, and C6 for protein synthesis material taught using the PjBL model. Quantitative data in the pretest and posttest found for the average, and then the increase from the pretest to the posttest is seen to conclude. Implementing the STEM-based Project Based Learning (PjBL) model can be carried out well at 74% in the implemented category. At the second meeting, the percentage was 85% in the implemented category. At the third meeting, the percentage was 93% in the immensely successful category. If averaged, the average percentage of implementation of the STEM-based learning project model is 84% in the implemented category. Implementing the STEM-based Project Based Learning (PjBL) model can improve students' learning outcomes and science process skills. Keywords: stem integration pjbl model, proses sains, and learning outcomes. Abstrak: Penelitian pembelajaran berbasis proyek ini bertujuan untuk memberikan alternatif penyelesaian pemasalahan pada matakuliah Biokimia II untuk meningkatkan kemampuan proses sains dan hasil belajar mahasiswa dalam menyelesaikan suatu permasalahan.. Data kualitatif ini diambil dari video kegiatan mahasiswa dan waktu presentasi proyek. Data kuantitatif, yaitu data hasil belajar mahasiswa C4, C5 dan C6 untuk materi sintesis protein yang diajar dengan model PjBL.Data kuantitatif berupa pretest dan posttest dicari rata-ratanya kemudian dilihat peningkatannya dari pretest ke posttes untuk menarik kesimpulan. Pelaksanaan model Project Based Learning (PjBL) berbasis STEM dapat terlaksana dengan baik sebesar 74% dengan kategori terlaksana. Pada pertemuan ke dua jumlah persentasinya 85% dengan kategori terlaksana. Pada pertemuan ketiga jumlah persentasinya adalah 93% dengan kategori sangat terlaksana. Jika dirata-ratakan maka diperoleh rata-rata persentasi pelaksanaan model Projek besed learning berbasis STEM Sebebsar 84% dengan kategori terlaksana. Implementasi model Project Based Learning (PjBL) berbasis STEM dapat meningkatkan hasil belajar dan keterampilan proses sains mahasiswa. Kata kunci: model pjbl terintegrasi stem, the science process, dan hasil belajar. DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp640-645